Television in Australia: capitals, tastes, practices and platforms. Issue 1 (May 2018) - Bennett, Tony; Gayo, Modesto; Rowe, David
This article discusses the findings of a national survey of the social organisation of television viewing practices in contemporary Australia. These questions are addressed through multiple correspondence analyses of the aspects of television practices and tastes covered in the survey. These go beyond channel and genre preferences to include a sample of Australian and overseas produced television programmes and of 10 Australian TV personalities. The differential distribution of tastes across Australian and overseas programmes also throws significant light on different investments in the national culture across different social groups. The survey data also includes evidence regarding viewing platform and device preferences. In concluding, the article reviews the evidence of a cluster analysis, registering the effects of major changes within the television field in Australia, including the decline of free-to-air and 'linear' viewing, the rise of streaming services and the erosion of brand loyalty as it relates to television channels.